NON-NATIVE PARENTS RAISING A BILINGUAL CHILD IN TURKEY - Ballıdağ, Sezgin; Dikilitaş, Kenan (Sustainable Multilingualism / Darnioji daugiakalbystė, 2024)
This case study explores the bilingual upbringing of a 5 year 2 months old child in Turkish and English through “non-native parents (NNP) strategy” within a context where English is neither the first nor the majority language of the community. Drawing on the Parental Discourse Hypothesis (Lanza, 1992) and Modeling Hypothesis (Comeau et al., 2003), the researchers examined not only the development of the child’s English, but also the approach of the father towards the child, and his self-perception as a father seeking opportunities to raise a bilingual child. The data were collected by means of a series of video recordings of the interaction between the child and the father, as well as via two semi-structured interviews with the father. The findings show that even quite limited exposure to a (second) language may lead to the acquisition of that language thanks to strict adherence to NNP strategy, and the parents’ concentrated efforts at refraining from code-mixing in their own speech.